The case of Little Red Riding Hood and the/MEGA Wolf with granny (Training and Practice : Journal of Educational Sciences, 2017)
Nowadays fairy tales are in abundance. Besides the classical stories we can find more and more modernized versions on the shelves of bookshops and on the internet as well. Usually it is the parents, the relatives and the teachers who try to find the books they consider to be the most suitable ones for the kids, which is not an easy task looking at the choice. As the number of modernized stories is increasing, we presupposed that it was (partly) because the children thought that they were closer to them and to the reality of everyday life. Therefore we had a concept that the children preferred them to the classical stories. We approached the question from the point of the view of the children. The present study is based on a survey conducted among thirty children in the second class in which we were curious to see how they received a classical story (namely Little Red Riding Hood) and its version of today. Analysing their answers we will present what they really think about an over-modernized tale.